PENERAPAN MEDIA POJOK BACA MELALUI GERAKAN LITERASI SEKOLAH UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN LITERASI SISWA - Nurhikmah, Nurhikmah; Idawati; Mariati (Information Technology Education Department, 2024)
The problem in this study is the low literacy of third grade students at SDN Sungguminasa V. This is evidenced by the observation results. This is evidenced by the results of observations; The purpose of this research is to describe the application of reading corner media through the School Literacy Movement (GLS) in improving the literacy comprehension skills of grade III students at SDN Sungguminasa V. The type of research is classroom action (PTK). The subjects of this study were third grade students consisting of 32 students, 15 male students and 17 female students. This research consists of 2 cycles, each cycle is carried out in 4 stages, namely planning, action, observation, and reflection and consists of 2 meetings. The results of the application of reading corner media are carried out with several steps, so that it can improve the literacy comprehension of third grade students of SDN Sungguminasa V. This shows that the literacy comprehension ability in cycle 1 has increased by 73% and in cycle 2 by 87.5%. This increase can be seen from the test results which show that the average student score increased after the reading corner media intervention. In addition, students also showed greater interest in reading about their reading. Based on these findings, it can be concluded that the implementation of the reading corner media through the School Literacy Movement (GLS) is an effective strategy to improve the literacy comprehension skills of Grade III students at SD Negeri Sungguminasa V.